2020
DOI: 10.1016/j.ijid.2020.09.1430
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated Isothermal Amplification (LAMP) for Identification of Pythium insidiosum

Abstract: Pythium insidiosum causes a life-threatening condition called pythiosis. High morbidity and mortality of pythiosis are consequences of delayed diagnosis. We aimed to develop a loop-mediated isothermal amplification (LAMP) assay for the rapid detection of P. insidiosum for use in remote areas, where pythiosis is prevalent. Methods: We designed four LAMP primers to amplify the rDNA sequence. A side-by-side comparison evaluated performances of LAMP and the previously-established multiplex PCR (M-PCR), using gDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…LAMP offers a rapid and high throughput alternative for detection of several types of disease-causing fungi viz. Candida albicans, Cryptococcus neoformans and Mucor racemosus ( Nakayama et al., 2017 ) , Trichosporonasahii ( Zhou et al., 2015 ), Aspergillus fumigatus ( Jiang et al., 2021 ) , Pythium insidiosum ( Htun et al., 2020 ) , etc. These studies have shown the requirement of a very low amount of DNA for LAMP assay which shows the high sensitivity of this method.…”
Section: Diagnostic Applications Of Conventional Lampmentioning
confidence: 99%
“…LAMP offers a rapid and high throughput alternative for detection of several types of disease-causing fungi viz. Candida albicans, Cryptococcus neoformans and Mucor racemosus ( Nakayama et al., 2017 ) , Trichosporonasahii ( Zhou et al., 2015 ), Aspergillus fumigatus ( Jiang et al., 2021 ) , Pythium insidiosum ( Htun et al., 2020 ) , etc. These studies have shown the requirement of a very low amount of DNA for LAMP assay which shows the high sensitivity of this method.…”
Section: Diagnostic Applications Of Conventional Lampmentioning
confidence: 99%
“…PCR for Pythium detection has rapidly evolved. The initial nested PCR had a sensitivity of around 90% with 80% specificity [ 51 ]. Duplex PCR targeting 18S rRNA and ITS showed 100% specificity but 91% sensitivity [ 49 ].…”
Section: Microbiological Laboratory Diagnosismentioning
confidence: 99%
“…The clinical manifestation of pythiosis can be similar to other fungal infections [11,24], leading to misdiagnosis, delayed treatment, and poor prognosis. Some diagnostic modalities have been developed and used for diagnosing pythiosis, such as culture identification and zoospore induction [25][26][27][28], histological examination (i.e., immunostaining) [29][30][31][32][33][34], serological tests [i.e., immunodiffusion (ID), Western blot (WB), enzyme-linked immunosorbent assay (ELISA), hemagglutination (HA), and immunochromatography (ICT)] [35][36][37][38][39][40][41], molecular assays (i.e., PCR and sequence homology analysis) [42][43][44][45], and proteomic approaches [46,47]. P. insidiosum exhibits limited sensitivity to conventional antimicrobial agents [48,49].…”
Section: Introductionmentioning
confidence: 99%